Membangun Daya Saing Wisata Sejarah, Budaya dan Religi dengan Meningkatkan Motivasi Wisatawan Berkunjung ke Pulau Penyengat Kepulauan Riau - Mulia Sosiady; Ermansyah Ermansyah (Policy, Law and Political Research Center, 2025)
One of the historical and cultural tourism destinations is the Cultural Potential of Penyengat Island. The island is renowned for its heritage, offering cultural uniqueness from the various sites located there. The combination of three types of tourism makes this island an attractive destination to visit. This research was conducted on Penyengat Island and at the Department of Culture and Tourism of Tanjung Pinang City, as well as at historical, cultural, and religious tourism sites on Penyengat Island. The population in this study consists of tourists visiting the Penyengat Island tourist area, the exact number of whom is unknown. To determine the sample size, the researcher used the Lameshow formula, resulting in a research sample of 96 tourists. The contribution of the psychological, cultural, social, and fantasy variables has an influence of 60.4%, while the remaining 39.6% is caused by other variables not examined in this study. Meanwhile, the Department of Culture and Tourism is developing tourist attractions in the Penyengat Island area to be more appealing by revitalising several historical, religious, and cultural tourist sites to make them more attractive to tourists.